#### Answer

$\frac{7}{6}$

#### Work Step by Step

$\frac{47}{36}-\frac{5}{36}=\frac{47-5}{36}=\frac{42}{36}=\frac{42\div6}{36\div6}=\frac{7}{6}$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$\frac{7}{6}$

$\frac{47}{36}-\frac{5}{36}=\frac{47-5}{36}=\frac{42}{36}=\frac{42\div6}{36\div6}=\frac{7}{6}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.